Political representation in bailed-out southern Europe: Greece and Portugal compared - Freire, A. (2015)
The emergence of the economic and financial crisis has already shown important electoral and political consequences in southern Europe. Drawing on the experience of two bailed-out countries, Greece and Portugal, we use original data collected before and after 2008 to examine how patterns of political representation have changed during this period. We argue that austerity measures have significantly affected the way MPs represent their electorates, namely in terms of policy congruence. In addition, the economic crisis has also deepened the legitimacy crisis in both countries. Finally, we find that the short-term impact of the crisis has had a greater impact on voters' attitudes than on those of their representatives.